Dreamed it : [large type] a Dreamwalker mystery - Toussaint, Maggie (A Dreamwalker mystery, 2020)
"When a Jane Doe is found in a suitcase, amateur sleuth Baxley Powell tries to identify the woman and her killer. A local woman vanishes, and Baxley fears the kidnapped woman will end up in a suitcase. Using normal and paranormal senses, Baxley matches wits with a cunning adversary"--